Pemanfaatan E-Banking dalam Industri Perbankan ditinjau dari Structure-Conduct-Performance Paradigm di Indonesia - M.Yusuf S. Barusman (Universitas Bandar Lampung (UBL), 2010)
Utilization of e-banking in the banking industry in Indonesia began in 2000, until the year 2008 a new 9 banks from 122 banks that use e-banking. The decision to implement e-banking is considered as a very courageous decision, since there is no legality that protects the use of e-banking. Since 2008, the government issued regulations on the Information and Electronic Transactions (ITE). In this research, the problems are: 1) How does the impact of utilization of e-banking in the development of the banking industry business strategy? 2) How to use ebanking relationships in the banking industry in terms of Structure-Conduct-Performace (SCP) paradigm? This research aims: 1) To determine the impact of utilization of e-banking in the banking industry business strategy development 2) To determine the utilization of ebanking relationships in the banking industry in terms of structure-conduct-performance (SCP) paradigm. SCP paradigm is a framework of analysis is the cycle that can be used as an analytical framework to ensure the sustainability of a business process. Herfindahl-Hirschman Index Value (HHI) was used to analyze the level of competition in the banking industry. The conclusions are: 1) business strategy by utilizing e-banking is a brave and risky decision (conduct) considering there has been no legality at that time, 2) Utilization of ebanking has made the market structure becomes more competitive as shown by the declining value of Herfindahl-Hirschman Index (HHI) of 1124.70 before any e-banking (moderates concentrated market structure) to 990.85 after the existing e-banking (un-concentrated market structure, 3) Utilization of e-banking positively affect the banking performance but not significantly different between the banks that already apply to those that not yet apply ebanking.—Pemanfaatan e-banking di Indonesia yang dimulai Tahun 2000, sampai dengan Tahun 2008 baru dilaksanakan oleh 9 bank dari 122 bank. Penerapkan e-banking merupakan keputusan berani, mengingat belum ada payung hukum yang melindungi. Baru pada Tahun 2008, pemerintah mengeluarkan peraturan tentang Informasi dan Transaksi Elektronik (ITE). Permasalahan dalam penelitian ini adalah: 1) Bagaimana dampak pemanfaatan e-banking dalam pengembangan strategi bisnis industri perbankan? 2) Bagaimana hubungan Jurnal Manajemen dan Bisnis Vol. 1 No. 1 Oktober 2010 : 1-20 2 pemanfaatan e-banking dalam industri perbankan ditinjau dari paradigma Structure-Conduct- Performace (SCP)? Penelitian ini bertujuan: 1) Untuk mengetahui dampak pemanfaatan ebanking dalam pengembangan strategi bisnis industri perbankan 2) Untuk mengetahui hubungan pemanfaatan e-banking dalam industri perbankan ditinjau dari paradigma structure-conduct-performance (SCP). Penelitian ini menggunakan metode deskriptif dengan menggunakan sumber data sekunder. Alat analisis yang digunakan adalah Paradigma SCP yakni kerangka analisis yang bersifat siklus yang dapat dimanfaatkan sebagai kerangka analisis untuk menjamin keberlanjutan proses bisnis. Untuk menganalisi tingkat persaingan digunakan Nilai Indeks Herfmdahl-Hirschman (Herfmdahl-Hirschman Index- HHI). Kesimpulan yang dihasilkan adalah:1) Strategi bisnis dengan memanfaatkan e-banking merupakan keputusan (conduct) yang berani dan beresiko mengingat pada saat itu belum ada payung hukumnya, 2) Pemanfaatan e-banking telah merubah struktur (structure) pasar menjadi lebih kompetitif yang ditunjukkan oleh turunnya Nilai Indeks Herfmdahl-Hirschman (HHI) dari 1124,70 sebelum ada e-banking (struktur pasar terkonsetrasi moderat) menjadi 990,85 setelah ada e-banking (struktur pasar tidak terkonsentrasi, 3) Pemanfaatan e-banking berdampak positif terhadap kinerja (performance) perbankan namun belum menunjukkan perbedaan yang berarti antara bank yang sudah menerapkan dengan yang belum menerapkan e-banking.